A arte inspira, cria e contagia: produção de sentidos e aprendizagens de professores provocados pela criação literária e audiovisual - Gonçalves, Rafael Salles (2020)
Grande do Sul, promoting spaces for literary and cinematographic creation among students and teachers, in an extension project promoted by the Federal University of Santa Maria. The activities included creation of short stories, arguments and synopses for cinema, scripts, short films and a video clip, in addition to promoting spaces for the exhibition of these works. The research aimed to discover what effects the creative processes and productions with the students had on their teachers. Furthermore, what knowledge was ignited by these experiences, and how they promote teaching training and self teaching training, show how the construction of art spaces in teaching takes place, and what other paths they can take to form teachers and transform teaching. We used as object of analysis a documentary produced with the Olavo Bilac Institute in 2017, after the end of the dynamics with the students. We also conducted virtual interviews with the group of teachers at the Humberto de Campos school, a socio-educational institution located in CASE-SM, which receives minors in deprivation of liberty. The interviews took place during the period of social isolation, between June and July 2020. As a result, we noticed several changes in the relationships of the school community, such as a closer relationship between teachers and students, also closer to the family and other communities around the educational institution with the school and with the students. We noticed teachers 'perceptions regarding the improvement in students' self-esteem, responsibility and commitment. We found great openness in the two education units for external projects, support and motivation for new proposals. We conclude that it is necessary to bring teachers closer to creative activities, either in their teaching training spaces or during activities developed with students or socio-educators.